The global crisis - a crisis of values and the domination of the weak by the strong - Meer, Fatima (1999)
This paper is a critique of the present mode of capitalist democracy from the ethico-moral viewpoint. The crisis of values is identified as the great bane of free market-led globalization. This trend has aggravated worldwide inequality, promoted terrorism and violence, created psychological anomie and triggered eco-logical disasters. Only a few business interests in the wealthier economies are gaining at the expense of humankind. The moral dimension of the government's role has been undermined by such profit-making free market gospel. The author contends that more than being just secular, democracy is a pre-social moral force and, as such, is perceived more proximately in the religious temper of a non-industrial society than in a mass industrial society. In the latter democracy is almost a farce with the periodic ritual of public voting as its main act. The paper castigates the global economy and global media which cleverly mastermined our lives, and pleads for a change of values which will make humans self-conscious and will restore their autonomy. - Reproduced
Keywords: Greenhouse effect; Globalization